BLOCKCHAIN FOR MARKETING: MOVING BEYOND HYPE TO APPLICATIONS IN PROVENANCE, LOYALTY, AND COUNTERFEIT PREVENTION - Dian Nofrianti; Lukmanul Hakim; Tibrani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This article examines the role of blockchain technology in marketing, moving beyond initial hype to explore its practical applications in provenance, loyalty programs, and counterfeit prevention. As blockchain matures, its core features—transparency, decentralization, and immutability—offer new opportunities to address longstanding challenges in marketing. Drawing on a narrative literature review and case-based analysis, this study identifies how blockchain enhances product traceability, enabling greater supply chain visibility and strengthening consumer trust through verifiable provenance. In loyalty programs, blockchain introduces tokenized and decentralized reward systems that increase flexibility, interoperability, and customer engagement. Additionally, blockchain-based authentication systems play a critical role in preventing counterfeiting, protecting brand equity, and ensuring consumer safety. The study also highlights key moderating factors, including technology adoption readiness, consumer awareness, and industry-specific requirements, which influence the effectiveness of blockchain applications. A conceptual framework is proposed to illustrate how blockchain-driven transparency and trust translate into improved marketing outcomes. This research contributes to bridging the gap between theoretical potential and real-world implementation, offering practical insights for marketers. Ultimately, blockchain’s value in marketing lies in its ability to deliver trust, enhance transparency, and create more secure and consumer-centric ecosystems.